PENGARUH SENAM ANTI NYERI HAID TERHADAP PENGURANGAN DISMENOREA DI SMA NEGERI 5 KOTA MAGELANG TAHUN 2014 - Miladiyah Rahmawati; Bekti Yuniyanti; mundarti mundarti (JURNAL KEBIDANAN, 2015)
One characteristic that marks the onset of women puberty are menstruating. When it comes, sometimes there are abnormalities or disorders associated with menstruation, that is dysmenorrhea or menstrual pain which forced her to restor reduce daily activity. One of dysmenorrheal precaution is doing gymnastics called anti-menstrual pain gymnastics (dysmenorrhea gym). When doing gymnastics, the endorphins hormone released as a neurotransmitter in the brain to reduce the transmission and perception of pain inthe body. This study was aimed to know the effect of anti-dysmenorrhea gymnastics exercise on reducing dysmenorrhea.The research method used in this study is a true experiment with a pretest-posttest design with control group. Randomization has been used in this design, it means the members of control and experimental group is grouped randomly. The object population in this study is the female students of State Senior High School 5 Magelang, as many as 281 students. Using 10% sampling technique, it was obtained 30 students to be tested. The control group and experimental groups each 15 students. Data collection tools were sheets of anti dysmenorrhea gym observation and sheets of pain scale observation. Data was analyzed using SPSS statistical software with the nonparametric Mann-Whitney test.The research data which analyzed using nonparametric Mann-Whitney showed P-value 0,000 and Z test -4,170. Because P-value 0,000 (less than) α (0,05) and Z test -1,96, then Ho is rejected, which means there is an effect of dysmenorrhoea gym on reducing female student’s menstrual pain in State Senior High School 5 Magelang , so anti-menstrual pain gymnastics can be used as an alternative therapy for the treatment of dysmenorrhea. And, for medical labor it will be good to deliver information and training of this anti-dysmenorrhea gymnastics to reduce dysmenorrhea in our society.